Pengembangan Bahan Ajar Berbasis E-Book pada Mata Kuliah Manajemen Strategi - Vicky Rizki Febrian; Annisaul Khairat; Muhammad Fazis; Husnani Husnani (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
The research aims to determine the feasibility or validity of teaching materials in the form of teaching materials in the form of E-Books as a medium for student learning in strategic management courses and to determine the practicality of teaching materials developed by researchers. The research method used is Research and Development (R&D) or research and development using the 4D development model consisting of define, design, develop, disseminate. The results of research and development of teaching materials in the form of E-Books are based on the assessment of material experts, media experts and linguists, namely the score obtained on the material expert aspect based on validator 1 is 87.50% and validator 2 is 85%, on the media expert aspect based on the Validator 1 is 90% and validator 2 is 80% and on the linguist aspect based on validator 1 is 85% and validator 2 is 80%. Then for the practicality of teaching materials in the form of E-Books get a score of 84.6%. From the results of this study it can be concluded that this research produces teaching materials in the form of e-books that are valid and practical. The results of the material validation reached the